Biosemiotics and ecological monitoring - Bruni , Luis Emilio (Sign Systems Studies, 2001)
During the recent decades, a global culrural-institutional network has gradually grown lip to project, implement, and use an enormous technological web that is supposed to observe, monitor, communicate, inventory, and assess our environment and its biodiversity in order to implement sustainable management models. The majority of "knowledge tools" that have been incorporated in the mainstream of this "techno-web" are amply based on a combination of mechanistic biology, genetic reductionism, economical determinism and neo-Darwinian cultural and biological perspectives. These approaches leave aside many of the qualitative and relational aspects that can only be grasped by considering the semiotic networks operative in complex ecological and cultural systems. In this paper, it is suggested that a biosemiotic approach to ecology may prove useful for the modelling process which in turn will allow the construction of meaningful monitoring systems. It is aJso advanced that it may as well serve to better integrate our understanding and monitoring of ecosystems into the cultural process of searching for (human) sustainability.